The universal solvent - Cheong, En Liang (2014)
“The piece aims to instigate reciprocation and exchange between individuals that emulates the evolution and changes in our social norms due to hyper-connectivity that has inevitably arose from the increase in one to many and its subsequent many to many networks. It can be seen as an interpretation of how we communicate with one another as of today and what we make of it; be it a necessary transition or a disruptive presence.”